2018
DOI: 10.1111/1742-6723.12947
|View full text |Cite
|
Sign up to set email alerts
|

Utility of community‐acquired pneumonia severity scores in guiding disposition from the emergency department: Intensive care or short‐stay unit?

Abstract: Community-acquired pneumonia severity scores had different strengths; SMARTCOP and CURXO were sensitive with potential to rule out severe disease, while the high specificity of CORB and CURB-65 facilitated identification of patients at high risk of requirement for ICU. Low severity scores were not useful to identify patients suitable for admission to short-stay units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…[21][22][23] While other studies have evaluated pneumonia and ICU severity scores, most failed to include patients in the ICU and others focused exclusively on patients with community acquired pneumonia. [24][25][26] Furthermore, these studies have either excluded those patients directly PA GE 6 admitted to the ICU or focused narrowly on ventilator associated pneumonia. [21,23,27] Other scores designed for use in patients with pneumonia requiring ICU admission, such as the PIRO (predisposition, insult, response, and organ dysfunction) include variables not easily obtained within 24h after admission, compromising routine use for early prediction of mortality and clinical trial enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] While other studies have evaluated pneumonia and ICU severity scores, most failed to include patients in the ICU and others focused exclusively on patients with community acquired pneumonia. [24][25][26] Furthermore, these studies have either excluded those patients directly PA GE 6 admitted to the ICU or focused narrowly on ventilator associated pneumonia. [21,23,27] Other scores designed for use in patients with pneumonia requiring ICU admission, such as the PIRO (predisposition, insult, response, and organ dysfunction) include variables not easily obtained within 24h after admission, compromising routine use for early prediction of mortality and clinical trial enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…After the initial diagnosis of CAP, the biggest challenge in the emergency department is to promptly recognize patients who might develop respiratory failure and multiple organ dysfunctions. Patients requiring mechanical ventilation or vasopressor support should be admitted to ICU as soon as possible, as delays in ICU admission have been related to worse outcomes [16][17][18].…”
Section: Why Is Community-acquired Pneumonia Severity Assessment Impomentioning
confidence: 99%
“…The IDSA/ATS major (need for mechanical ventilation or septic shock) and minor (respiratory rate !30 breaths/min, PaO2/FiO2 ratio 250, multilobar infiltrates, confusion or disorientation, blood urea nitrogen !20 mg/dl, leukocyte count <4 Â 10 9 cells/ l, platelets count <100 Â 10 9 cells/l, temperature < 368C and hypotension requiring aggressive fluid resuscitation) criteria have been proposed to identify patients with severe CAP requiring ICU admission. Minor criteria are easy to use and have shown high specificity (91.7%) in predicting ICU admission and the need for intensive respiratory or vasopressor support [17,22]. Even in the absence of major criteria, the presence of at least three minor criteria has been associated with complications and a high 30-day mortality risk [22,23].…”
Section: Why Is Community-acquired Pneumonia Severity Assessment Impomentioning
confidence: 99%
“…The severity scores of CAP have different strengths and weaknesses. CURB-65 had high specificity to determine of patients at high risk of requirement for ICU (17). In a systematic review and meta-analysis showed that severity scales to predicting mortality in CAP patients had good negative predictive values for mortality (18).…”
Section: Discussionmentioning
confidence: 99%